Cardiological evaluation for patients with congenital bone marrow disorders - Marwa Hassan Ali; Enas Abdelah Ali; Mohamed Ali Hegazi; Mona Mohamed Hamdy Mahmoud (Cairo : Marwa Hassan Ali, 2010)
This study was conducted on 30 patients with bone marrow failure divided into 2 groups: Congenital group [included 20 patients diagnosed as congenital bone marrow disorders] and acquired group [included 10 patients diagnosed as acquired aplastic anemia (serving as a comparative group)]. They were subjected to full history taking, clinical examination, laboratory investigations and cardiac evaluation by chest X-ray, electrocardiography (ECG) and echocardiography
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: Cardiological evaluation; Congenital bone marrow disorders; Pediatrics